The Effect of Relationship Marketing capability of Small and Medium-sized Enterprises on the Corporate performance - Focusing on the Mediation Effect of Trust - - Yen-yoo You, Dong-su Kim, (International Journal of Advanced Science and Technology, 2020)
Background/Objectives: The purpose of this study is to study how the marketing capabilities of the traditional marketing strategy 4P and the interactive marketing skills such as relationship marketing and content marketing, which form, maintain, and develop relationships with customers, affect the performance of the enterprise.